Factors Associated with the Use of Outcome Measures among Physiotherapists Working in Neurorehabilitation Units in Tertiary Hospitals of North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The use of standardised outcome measures (SOMs) is an essential part of rehabilitation and is widely endorsed as an excellent practice.Aim:The purpose of this descriptive study was to identify the factors associated with the use of OMs among physiotherapists working in neurorehabilitation units in tertiary hospitals of North-Western Nigeria.Materials and Methods:Physiotherapists managing neurological conditions in North-Western Nigeria were asked to complete a structured self-administered questionnaire that has two sections. Section I comprises items consisting of demographic information and Section II comprises items regarding the knowledge, attitude, use, perceived benefits and factors that hinder the use of SOMs among physiotherapists managing neurological conditions.Results:over 72.9% of the respondents were familiar with OMs; majority (77.1%) had poor attitude even though they had positive perception about the use of OMs. The respondents reported four most crucial factors hindering the use of OMs in neurological physiotherapy practice in tertiary hospitals in North-Western Nigeria, which are unavailability of appropriate tools, lengthy completion time of OMs, inadequate office space and lack of training on how to use OMs.Conclusion:The main findings of this study revealed that majority of the Participants were aware of the use of outcome measures in clinical practice, they perceived it as essential and useful, however, they have poor attitude and seldom make use of the Oms.